Slocum and the big timber terror - Logan, Jake (Logan, Jake. Slocum, 2014)
"Caught in a snowstorm in the Cascade Range, Slocum tries to bed down in the heavy Oregon woods. But when he finds himself in the crosshairs of a pair of inhuman glowing eyes--accompanied by a terrifying screech and an unbearable stench--he realizes that he is most certainly not alone. He's just run into a legendary local nightmare, one that is about to unleash a bloody storm" --